Investigation of the physicochemical parameters of drinking water in Herat province and its comparison with World Health Organization standards - Safiullah Fetrat; Safiullah Islam (Discover Water)
Abstract The physical, chemical, and microbial parameters of drinking water are the basis for judging if it is potable. Undesirable changes in these parameters can threaten the users’ health. Therefore, the present study aimed to evaluate the physicochemical qualities of drinking water in Herat Province and compare them with the WHO standards. 45 drinking water samples were collected from Herat Province to undergo physicochemical tests. This study was conducted in 2023. The mean values measured for parameters such as temperature, turbidity, electrical conductivity (EC), pH, total dissolved solids (TDS), fluoride, nitrate, calcium, magnesium, and total hardness (TH) were 26.3℃, 0.93 NTU, 1328 μS/cm /cm, 7.32, 576.8, 0.26, 12.014, 6.8, 11.25, and 58.33 mg/L, respectively. The turbidity, TDS, and EC of some samples were higher than the highest desirable limit (HDL) but lower than the Maximum allowable limit (MAL). Also, there is a shortage of fluoride in samples. The Water Quality Index (WQI) shows that the quality of drinking water in Herat Province is classified as Poor.